Increased percentages of PD-1 on CD4+ T cells is associated with higher INF-γ production and altered IL-17 production in patients with systemic lupus erythematosus. (August 2014) - Dolff, S; Quandt, D; Feldkamp, T; Jun, C; Mitchell, A; Hua, F; Specker, C; Kribben, A; Witzke, O; Wilde, B
<x xml:space="preserve">Abstract</x> Objectives: Programmed death (PD)-1 is a cell death receptor that, upon stimulation, leads to apoptosis. Previous studies have shown alteration of PD-1 expression on T cells and PD-1 genes in patients with systemic lupus erythematosus (SLE). The aim of this study was to assess the expression of this receptor on effector T cells in patients with SLE. Method: In this study we enrolled 32 SLE patients and 31 healthy controls. T cells from peripheral blood were analysed by flow cytometry for the expression of PD-1. Interferon (IFN)-γ and interleukin (IL)-17-producing cells were investigated for the expression of this co-stimulatory marker. Results: Percentages of CD4+ T cells expressing PD-1 were significantly increased in patients with SLE compared to healthy controls. The percentage of PD-1 expression was correlated with the production of INF-γ (r = 0.83, p < 0.0001). We also investigated the production of IL-17 by PD-1+ CD3+ T cells. Inactive patients (3.2 ± 1.2% vs. 5.9 ± 3.5%, p = 0.002) and patients without lupus nephritis (LN) (3.2 ± 1.5% vs. 5.9 ± 3.5%, p = 0.005) showed lower levels of IL-17 compared to healthy controls. Conclusion: We have demonstrated increased expression of PD-1 on CD4+ T cells in SLE patients and an association between PD-1 expression on CD4+ T cells and IFN-γ expression on CD3+ T cells. We have also shown that there is an altered subset of PD-1+ T cells in inactive patients and patients without LN producing lower amounts of IL-17.